Effects of altitude training on the state of function of elite swimmers - Ruan, E.; Sun, Q.; Li, Z. (2001)
The purpose of this study is to analyze the effects of high altitude training on the state of function of elite swimmers. Nine Chinese elite Swimmers including Le Jing-yi, champion of women`s 100m freestyle at 26th Atlanta Olympic Games, had four weeks of high altitude training in Kunming, China (1891m above sea level) before 26th Olympic Games. After the training, they returned to Beijing for five weeks. We tested Hb, BUN, Cortisol, FT and SIL-2R during the period. The findings were as follows: 1. In the second week of high altitude training, their Hb began to rise to 16.9±2.1g% compared with 14.8±2.4g% in the first week (p<0.05). Returning from altitude training, their Hb remained the same for some time, then began to decrease every week. In the fifth Week, it dropped to 15.0g%. 2. During the four-week high altitude training, BUN was always above 20.0mg%, higher than it was when they were at the land level. The better their performance, the lower their BUN. Their recovering value also decreased every week. Returning from the altitude, their motivation value dropped significantly. There was no significant difference in the recovering value between the altitude and the land level. 3. In the second week and the third week at the altitude, their Cortisol was 13.2±3.8ug/dl and 13.9±4.5ug/dl respectively, much higher than 11.0±3.1ug/dl in the first week (p<0.05). In the fourth week, it dropped to 12.0±4.8ug/dl. After altitude training, their Cortisol of the first week and the third week were 10.6±2.9ug/dl and 16.2±5.0ug/dl respectively. 4. At the high altitude, there was a tendency for FT to decrease week after week. FT increased when leaving the high altitude. FT rose to its highest point in the second week and began to drop in the fourth week. The athlete`s organs were in stress states in high altitude training. Catabolism was faster than anabolism, with C/FT rising to the highest point in the fourth week. During the three weeks after leaving the high altitude, C/FT began to drop (p<0.05).